Evaluation of the Quality of Student Memorization Based on Fahmil (Understanding) of The Qur'an in Tahfizh Al-Qur'an Program at SDIT Plus Usman Bin Ali Medan - Abd Rahman (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study evaluates the quality of Qur’an memorization based on fahmil (understanding) at SDIT Plus Usman Bin Ali Medan. The research is motivated by the tendency of tahfizh learning to emphasize memorization quantity rather than comprehension and internalization of Qur’anic values. A qualitative evaluative approach using the CIPP model (Context, Input, Process, Product) was employed. Data were collected through observation, interviews, and documentation involving principals, tahfizh teachers, students, and parents. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The results indicate that fahmil-based evaluation has been implemented by integrating meaning comprehension into memorization activities. Students are assessed not only on memorization fluency but also on understanding and interpretation of verses. This approach improves memorization quality and religious character. However, challenges remain, including the absence of standardized assessment instruments and limited teacher competence in Qur’anic interpretation skills.